Diversity, equality and achievement in education - Knowles, Gianna; Lander, Vini.; Sage eBooks (London : SAGE, 2011)
Most classrooms contain children from a variety of backgrounds where home culture, religious beliefs and the family's economic situation all impact on achievement. This text explains how teachers can recognise such diversity and establish fair respectful, trusting and constructive relationships with children and their families.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Inclusive education; Multicultural education; Effective teaching; Children of minorities -- Education; Children with social disabilities -- Education; Electronic books